Aortopulmonary window and right aortic arch in a fetus - Zidere, Vita; Vigneswaran, Trisha; Lloyd, David; To, Meekai; Pushparajah, Kuberan; Austin, Conal (Prenatal Cardiology, 2020)
We present the first description of a prenatal diagnosis of aortopulmonary window in association with right aortic arch and perimembranous ventricular septal defect. The diagnosis was made with fetal echocardiogram and subsequently confirmed using 3D motion-corrected fetal cardiac magnetic resonance imaging and postnatal echocardiogram. The genetic testing revealed normal array CGH, and the child underwent successful surgery in the neonatal period.